Аналитическое определение момента инерции ротора ударно-центробежной дробилки - Зиборов, К. А.; Логинова, А. А. (Видавництво НГУ, 2015)
В работе аналитически определяется осевой момента инерции ротора ударно‐центробежной дробилки относительно оси его вращения.

The paper analytically determined by the axial moment of inertia of the rotor centrifugal crusher shock relative to the axis of rotation.
Analytical determination of the rotor inertia moment of centrifugal crusher
Keywords: ударно центробежная дробилка; осевой момент инерции; ротор; Shock centrifugal crusher; axial moment of inertia; rotor